Design and fabrication of control system-based ISO pulse generator for electrical discharge machining. (1st January 2013) - Muthuramalingam, T.; Mohan, B.
Electrical discharge machining (EDM) is good example for mechatronics application, in which, the material is removed by thermal energy. The thermal energy is produced by applying DC pulses between tool electrode and work piece. The characteristics of DC pulses are determined by the pulse generators. Due to its high material removal nature, transistor pulse train generator is commonly employed. Since EDM process has stochastic nature, transistor pulse generator produces high surface roughness. To produce better product quality, a constant discharging current is needed throughout the process. In this research, an ISO duration current pulse generator has been designed and developed for obtaining good surface finish. It is found that modified ISO pulse generator could produce better surface finish.